2021
DOI: 10.1111/irfi.12343
|View full text |Cite
|
Sign up to set email alerts
|

Physical proximity, corporate social responsibility, and the impact of negative investor sentiment on stock returns: Evidence from COVID‐19 in China

Abstract: Using the Hubei province in China as the COVID‐19 pandemic epicenter and January 23, 2020 as the event date (the date the Chinese government announced the lockdown of Wuhan, the provincial capital), we document that while Chinese firms generally exhibited negative cumulative abnormal returns (CARs) around the event date, firms located far from the Hubei province experienced relatively less adverse impact by way of negative CARs than firms located close to and in the province. Moreover, firms that engaged stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…This leads to information discovery and market efficiency (Vozlyublennaia 2014). Most existing studies document that such adverse events have homogeneous effects on stock prices [Topcu and Gulal (2020); Ashraf (2020a, b;Phan and Narayan (2020); Erdem (2020); Alexakis et al (2021); Zhai et al (2021); Dharani et al (2022)]. Therefore, the present study examines whether the Covid-19 pandemic has homogeneous effects on stock returns in India.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This leads to information discovery and market efficiency (Vozlyublennaia 2014). Most existing studies document that such adverse events have homogeneous effects on stock prices [Topcu and Gulal (2020); Ashraf (2020a, b;Phan and Narayan (2020); Erdem (2020); Alexakis et al (2021); Zhai et al (2021); Dharani et al (2022)]. Therefore, the present study examines whether the Covid-19 pandemic has homogeneous effects on stock returns in India.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, to understand the psychology of people in the stock market, Isen and Simmonds (1978) provide evidence that people in a good mood make optimistic decisions, whereas people in a bad mood make pessimistic decisions. Similarly, Zhai et al (2021) document that major events such as the global financial crisis of 2008, terrorist attacks of 2001, Ebola outbreak of 2014, and current Covid-19 pandemic induce pessimistic investment decisions. Thus, these adverse events affect investor psychology and lead to antagonistic changes in stock prices.…”
Section: Introductionmentioning
confidence: 99%
“…Although the research on the relationship between CSR and communication during the pandemic period is not very comprehensive, many scholars have demonstrated that CSR can perform the same effect during the COVID-19 pandemic, reducing the negative effect of the crisis. It was demonstrated that companies with more CSR activities such as corporate donation (Zhai et al, 2022) were less affected by the stock price drop caused by the pandemic (Ding et al, 2020), and outside investors have more rewarded companies with an elevated level of environmental responsibility (Garel and Petit-Romec, 2021). This underlines that farsighted entrepreneurs will foster the relationship with the stakeholders through the CSR activities, with a long-term perspective (Waheed and Zhang, 2022), while myopic entrepreneurs will concentrate on the core operating business and the short-term survival.…”
Section: MDmentioning
confidence: 99%
“…Although the research on the relationship between CSR and communication during the pandemic period is not very comprehensive, many scholars have demonstrated that CSR can perform the same effect during the COVID-19 pandemic, reducing the negative effect of the crisis. It was demonstrated that companies with more CSR activities such as corporate donation (Zhai et al. , 2022) were less affected by the stock price drop caused by the pandemic (Ding et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, because the global widespread of the pandemic is more pronounced, the urgent implementation of more strategic CSR is required for at least two reasons (He & Harris, 2020 ). First , CSR may give insurance value by safeguarding firm shareholders’ wealth (Zhai et al, 2022 ). Firms that participated in CSR actions reduced company risks (Ziogas & Metaxas, 2021 ).…”
Section: Introductionmentioning
confidence: 99%